2, 6‐Bis(diazaboryl)pyridine: A Superbasic Sterically Demanding Pyridine Ligand. Issue 45 (21st July 2017) - Schröder, Jan; Himmel, Daniel; Böttcher, Tobias
Abstract: Herein a convenient one‐pot route to a sterically demanding superbasic pyridine is presented. Functionalization of the 2‐ and 6‐positions with the strongly σ‐donating boryl‐groups shifts the calculated gas phase basicity of the pyridine nitrogen atom to 1012 kJ mol −1, which outperforms the "proton sponge" 1, 8‐bis(dimethylamino)naphthalene (996 kJ mol −1 ). The diazaboryl groups are oriented orthogonally to the pyridine ring and do not block the N‐position, which resembles the geometry of commonly used N‐heterocyclic carbenes. This allows the substituted pyridine to be used as a neutral N‐donor ligand in coordination chemistry that is demonstrated herein with the Lewis adducts of haloboranes. Contrary to NHCs, which can form extraordinarily stable adducts, the pyridine ligand is intended to act as a weaker‐coordinating alternative and could allow for alternative ligand chemistry. Abstract : A superbasic pyridine ligand : A pyridine substituted with diazaboryl groups at the 2‐ and 6‐positions is presented. The strongly σ‐donating diazaboryl groups increase the energy of the pyridine nitrogen lone pair and make it become more basic than the "proton sponge" 1, 8‐bis(dimethylamino)naphthalene. The N‐position is not blocked, but is sterically protected, which renders this pyridine a promising ligand for coordination chemistry.